The Expressive Potential of Neologisms as the Catalyst for Grotesque Generation [Based on Excerpts from the Novel Cosmos by W. Gombrowicz] - Хамзе, Димитрина (Poznańskie Studia Slawistyczne, 2015)
The relatively scarce surveys in the field of neologisms and the complete lack of a large scale search approach, which could unveil their diverse and multifunctional inherent capacity, posits the goal of the present survey as one of many possible vistas for the overture of their expressive potential as a powerful factor for triggering the grotesque. The results of the survey confirm the hypothesis related to the existential and expressive dynamics of neologisms – as backed by way of a plethora of linguistic means – acting as the generator of numerous functions: ludic, spontaneous, ontological and epistemological, esoteric, ritualistic and magic, bewitching, prophetic, integrative, transcending and demiurgic, communicative and entertaining.